N ANALYSIS OF TRANSLATION OF LANGUAGE STYLEIN DAN BROWN'S NOVEL ENTITLEDDIGITAL FORTRESS AND ITS TRANSLATED VERSION ENTITLED DIGITAL FORTRESS (BENTENG DIGITAL) - Dina Racmawati, - (2009)
This study is entitled "An Analysis of Translation of Language Style in Dan Brown's Novel Entitled Digital Fortress and Its Translated Version Entitled Digital Fortress (Benteng Digital)". It is aimed at finding out the category of language style spoken by some characters in the novel and the translation methods used in translating the dialogue. The scope of the study is limited to the selected dialogues from chapter 1 to chapter 23 that are found in the novel. The study employs a descriptive qualitative method since it produces descriptive data from the object of the study. The data were collected from both version of the novel; original version and translated version and the analysis conducted through close reading method. The result of the study shows that mostly the dialogues are translated by using Faithful translation method. In this method, the SL texts are translated based on the contextual meaning of the source language by paying attention to the grammatical construction. In both versions there is no frozen style. The style that mostly used in both novel is the formal style.